Days Needed to Characterize the Healthfulness of a Typical Dinner Meal in Direct Observational Research: Mixed Methods Study - Tate, Allan; Trofholz, Amanda; Miner, Michael; Berge, Jerica (JMIR Publications, 2021)
BackgroundPrior research around the home meal environment has demonstrated that family meals are associated with positive health outcomes for children and adolescents. Researchers have begun using direct observational methods to understand key aspects of family meals such as meal healthfulness and family meal frequency to explain the protective nature of family meals. Direct observational research, however, can be resource intensive and also burdensome for participants. Information about the number of days needed to sufficiently characterize typical meal healthfulness using direct observational research methods is needed. ObjectiveThe current study aimed to produce guidance about the number of meals necessary to approximate typical meal healthfulness at the family dinner meal occasion in a direct observational, mixed methods study of the home food environment. MethodsFamilies were recruited between 2012-2013 from primary care clinics in the Minneapolis-St Paul metropolitan area (N=120). A total of 800 meals were collected as part of the Family Meals LIVE! mixed methods study. The Healthfulness of Meal Index was used to evaluate meal dietary healthfulness of foods served at 8 family meal occasions. Participating families were provided an iPad (Apple Inc) and asked to video-record 8 consecutive days of family dinner meals with a minimum of two weekend meals. After the meal, families completed a meal screener, which is a self-reported, open-ended measure of the foods served at the meal. ResultsWeekend and weekday meals differed in their measurement of meal healthfulness, indicating that at least one weekday and one weekend day are necessary to approximate meal healthfulness. Single-day measurement mischaracterized the strength of the relationship between the quality of what was served and intake by almost 50%, and 3 to 4 observation days were sufficient to characterize typical weekly meal healthfulness (r=0.94; P<.001). ConclusionsRelatively few direct observational days of family meals data appear to be needed to approximate the healthfulness of meals across 1 week. Specifically, 1 weekday and 1 weekend observation are needed, including a total of 3 to 4 days of direct observational meal data. These findings may inform future direct observational study designs to reduce both research costs and participant burden in assessing features of the meal environment.